2004
DOI: 10.1016/j.tws.2004.03.015
|View full text |Cite
|
Sign up to set email alerts
|

Flexural–torsional behavior of thin-walled composite beams

Abstract: Citation: Vo, Thuc and Lee, Jaehong (2007) Flexural-torsional behavior of thin-walled closed-section composite box beams. Engineering Structures, 29 (8) Northumbria University has developed Northumbria Research Link (NRL) to enable users to access the University's research output. Copyright © and moral rights for items on NRL are retained by the individual author(s) and/or other copyright owners. Single copies of full items can be reproduced, displayed or performed, and given to third parties in any format or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
44
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 73 publications
(45 citation statements)
references
References 10 publications
(7 reference statements)
1
44
0
Order By: Relevance
“…The table shows an excellent agreement between the predictions of the present model and the results of the other models mentioned, especially the results of Lee [8]. Moreover, the present results based on plane stress conditions are found to be closer to the results produced by ABAQUS [20] than the results in [8], [19]. It is further observed that in all cases convergence of the results was achieved using only two elements with the approach proposed herein.…”
Section: Simply Supported I Beam Subjected To Uniformly Distributed Tsupporting
confidence: 81%
See 4 more Smart Citations
“…The table shows an excellent agreement between the predictions of the present model and the results of the other models mentioned, especially the results of Lee [8]. Moreover, the present results based on plane stress conditions are found to be closer to the results produced by ABAQUS [20] than the results in [8], [19]. It is further observed that in all cases convergence of the results was achieved using only two elements with the approach proposed herein.…”
Section: Simply Supported I Beam Subjected To Uniformly Distributed Tsupporting
confidence: 81%
“…The values of deflection at the centre of the beam and the bending slope at its supports obtained in the present analysis are presented in Table 1 and Table 2, respectively. The results for the deflections are compared with those of Lee [8] and Lee and Lee [19] in Table 1. Lee [8] considered the effect of transverse shear deformation, whereas the study of Lee and Lee [19] is based on classical lamination theory.…”
Section: Simply Supported I Beam Subjected To Uniformly Distributed Tmentioning
confidence: 99%
See 3 more Smart Citations